Comparison of the Catalytic and Immunological Properties of β-Glucosidases from Three Strains of Saccharomyces lactis - Marchin, George L. (1969)
β-Glucosidase from Saccharomyces lactis strains Y-123 (B(h)), Y-14 (B(m)), and Y-1057A (B(1)) was partially purified. The pH optima, Michaelis constants, and activation energies were determined for the hydrolysis of p-nitro-phenyl-β-d-glucoside by each of the enzymes. Differences among these constants were not enough to account for the low specific activity of β-glucosidase in strains Y-14 and Y-1057A. Enzyme-inhibitor constants were measured for a series of alkyl and aryl glucosides. In general, the three enzymes are arylglucosidases. Tris(hydroxymethyl)-aminomethane inhibited all three enzymes in an uncompetitive fashion. The inhibition was antagonized by Mg(++). An antiserum was prepared to the highly purified (200-fold) β-glucosidase from strain Y-123. The nature and degree of cross-reaction between the three β-glucosidases was investigated by double diffusion in agar and neutralization tests. Spur formation in the immunodiffusion tests and similar equivalence points in the neutralization tests indicated a strong degree of cross-reaction between the three enzymes. The ratio of enzyme activity to antigenicity was used to compare the relative molecular activity of β-glucosidase in the three strains. Each strain produced the same amount of β-glucosidase per milligram of cell protein. The results are consistent either with a lower turnover number for the β-glucosidase in strains Y-14 and Y-1057A or with the production of β-glucosidase with a “normal” turnover number and enough cross-reacting material to effectively reduce the specific activity to the observed levels.